Digoxin reduces the incidence of prostate cancer but increases the cancer‐specific mortality: A systematic review and pooled analysis. (19th August 2021) - Zhao, Shankun; Li, Xin; Wu, Weizhou; Liu, Shixiong; Shen, Maolei; Zhang, Zuzhao; He, Jian
Abstract: Digoxin, a commonly used drug for congestive heart failure and cardiac arrhythmias, has been reported to exert cytotoxic and apoptosis‐inducing effects on prostate cancer (PCa) cells. In this study, we aimed to perform a pooled analysis to summarise all the evidence related to the effects of digoxin on PCa development. Four electronic databases were systematically searched to filter the eligible studies. The hazard ratio (HR) with its 95% confidence interval (CI) was calculated. This study was registered on PROSPERO (ID: CRD42021226885). Ten clinical studies with a total of 108, 444 participants (15, 835 individuals were digoxin users) were included. The pooled result from 6 included studies demonstrated that digoxin usage was correlated with a significant decrease in PCa risk (adjusted RR = 0.892, 95% CI: 0.799–0.997, p = .044) when compared with the nonusers. Synthetic result of 4 eligible studies revealed that digoxin significantly correlated with higher prostate cancer‐specific mortality than the controls (adjusted HR = 1.142, 95% CI: 1.005–1.297). No statistical heterogeneity was detected during this analysis (all I 2 < 50%, p > .1). Our study confirmed a preventive effect of digoxin usage for the risk of PCa in men. However, digoxin use was associated with a significantly elevated risk of prostate cancer‐specific mortality. This finding needs more well‐designed studies to better interpret the causality.